PENDUGAAN POTENSI DAN PEMANFAATAN SUMBERDAYA AIR DI SUB DAS CIWIDEY (Studi Kasus Cagar Alam Gunung Tilu Jawa Barat) - , Matheas Ari Wibawanto; , Prof. Dr. Ir. Djoko Marsono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The utilization of the water resource in the natural preservation of Gunung Tilu has benefited the surrounding people. However, the data of the potentials of the water resource in the natural preservation of Gunung Tilu and its utilization pattern have not acurately been determined, well-understood and recognized by all parties concerned. The predictable consequence was the low support of the people and the local government for the preservation effort made in the natural preservation of Gunung Tilu. The study aimed at predicting the potential of the water resource in Ciwidey Water Catchment Area and the natural preservation of Gunung Tilu situated in Ciwidey Water Catchment Area and finding out the utilization pattern of the water resource by the people of Pasir Jambu subdistrict of domestic use and agriculture use. The water balance as indicated by the water critical index in the village was used to investigate the role and the contribution of the water resouce of the natural preservation of Gunung Tilu in answering the needs of the people of Pasir Jambu subdistrict for water. The potential of the water resource of the natural preservation of Gunung Tilu situated in Ciwidey water catechment area was predicted using Mock model analysis and weighing the simulation volume of the Ciwidey water catchment area based on water flow coefficient transformation process into the infiltration/percolation in each of the existing land uses units in the water catchment area. The predicted potential of the water resource of Ciwidey water catchment area was 11.637 m3/second with the highest mean debet of 21.269 m3/second took place in the first and second weeks of February and the lowest mean debit of 1.6376 m3/second in the third and fourth weeks of September. The predicted mean potential of the water resource of the natural preservation of Gunung Tilu was 1.39 m3/second with the highest mean debet of 2.759 m3/second took place in the first and second weeks of February and the lowest mean debit of 0.212 m3/second in the third and fourth weeks of September. The predicted mean need for water in Pasir Jambu subdistrict was 1.201 m3/second with the highest need of 1.91 m3/second took place at the end of November and at the beginning of December and the lowest need of 0.532 m3/second took place at the beginning of September to the end of October. The contribution of the water resource of the natural preservation of Gunung Tilu in dry season has not been able to answer the need of the people of Pasir Jambu subdistric for water as clearly indicated by the high water critical index, which was above 100% at the end of June to the middle of October.